Domiciliary non-invasive ventilation for recurrent acidotic exacerbations of COPD: an economic analysis. Issue 10 (26th September 2003) - Tuggey, J M; Plant, P K; Elliott, M W
Abstract : Background: Patients with chronic obstructive pulmonary disease (COPD) pose a significant burden to healthcare providers with frequent exacerbations necessitating hospital admission. Randomised controlled data exist supporting the use of acute non-invasive ventilation (NIV) in patients with exacerbations of COPD with mild to moderate acidosis. The use of NIV is also described in chronic stable COPD, with evidence suggesting a reduction in hospital admissions and general practitioner care. We present economic data on the impact of domiciliary NIV on the need for admission to hospital and its attendant costs. Methods: A cost and consequences analysis of domiciliary NIV based on a before and after case note audit was performed in patients with recurrent acidotic exacerbations of COPD who tolerated and responded well to NIV. The primary outcome measure was the total cost incurred per patient per year from the perspective of the acute hospital. Effectiveness outcomes were total days in hospital and in intensive care. Results: Thirteen patients were identified. Provision of a home NIV service resulted in a mean (95% CI) saving of £8254 (£4013 to £12 495) (€11 720; €5698 to €17 743) per patient per year. Total days in hospital fell from a mean (SD) of 78 (51) to 25 (25) (p=0.004), number of admissions from 5 (3) to 2 (2) (p=0.007), and ICU days fell from a total of 25 to 4 (p=0.24). Outpatient visits fell from a mean of 5 (3) to 4 (2) (p=0.14). Conclusions: This study suggests that domiciliary NIV for a highly selected group of COPD patients with recurrent admissions requiring NIV is effective at reducing admissions and minimises costs from the perspective of the acute hospital. Such evidence is important in obtaining financial support for providing such a service.